Morphological ontogeny in Tenuipalpus orilloi Rimando (Acari: Tenuipalpidae) - Xu, Yun; Zhu, Yu-Zhen; Wu, Jie-Qin; Zhang, Fei-Ping (Zootaxa, 2019)
The ontogenetic stages of a tenuipalpid mite, Tenuipalpus orilloi Rimando, are described with detailed illustrations of the larva, protonymph, deutonymph and adult male and female specimens recently collected from Evodia lepta (Spreng.) Merr. (Rutaceae) in the Fujian province of China. The ontogenetic changes in idiosomal and leg chaetotaxy are discussed.